Metodología A.B.J y su incidencia en el aprendizaje significativo de los estudiantes de la Parroquia Dr. Camilo Ponce Cantón Babahoyo periodo 2024-2025 - García Troya, Nayeli Estefania (2025)
The research examined the implementation of the Game-Based Learning (GBL) methodology and its impact on meaningful learning. The background showed relevant studies such as that of Martínez et al. (2023), which revealed a 35% increase in comprehension levels through GBL, and González-Sánchez (2024), which demonstrated 28% more knowledge retention compared to traditional methods. The problem identified was the limited effectiveness of traditional methodologies at the Leonardo Nagua Molina Educational Unit. The main objective was to determine the impact of the GBL methodology on meaningful learning of 4th grade students during 2024-2025. The research adopted a mixed approach, combining quantitative and qualitative methods. The population comprised 80 students, 2 teachers, and 80 parents, with a specific sample of 76 students, 2 teachers, and 22 parents of 4th grade students. Collection techniques included observation, teacher interviews, and parent surveys. The results suggested a significant increase in motivation, active participation and knowledge retention through the implementation of BBJ. An improvement in academic performance and development of social skills was evident. In conclusion, the BBJ methodology proved to be an effective tool to promote meaningful learning, improving understanding, retention and practical application of knowledge in basic education students. This research contributed significantly to the educational field, providing empirical evidence on the effectiveness of innovative methodologies in the local context and establishing bases for future implementations.